The Neurobiology of Parental Behavior - Numan, Michael. (Hormones, Brain, and Behavior, 2003)
In addition to filling a need within the field of parental behavior, this book contributes importantly to the growing area of emotional and motivational neuroscience. A major part of neuroscience research at the whole organism level has been focused on cognitive neuroscience, with an emphasis on the neurobiology of learning and memory, but there has been a recent upsurge in research which is attempting to define the neural basis of basic motivational and emotional systems which regulate such behaviors as food intake, aggression, reproduction, reward-seeking behaviors, and anxiety-related behaviors. In this book the emphasis is on the research findings obtained from rodents, sheep and primates. The authors' goal, of course, was to provide a foundation that may help us understand the neurobiology of human parental behavior. Indeed, the last chapter attempts to integrate the non-human research data with some human data in order to make some inroads toward an understanding of postpartum depression, child abuse, and child neglect. Clearly, motivational and emotional neuroscience has close ties to psychiatry, and this connection will be very evident in the final chapter. By understanding the neurobiology of parental behavior we are also delving into neurobiological factors which may have an impact on core human characteristics involved in sociality, social attachment, nurturing behavior, and love. In this very violent world, it is hard to conceive of a group of characteristics that are more worthy of study.